2006
DOI: 10.1002/ccd.21030
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of secundum atrial defect in small children

Abstract: Patients < or =15 kg requiring ASD closure form a special population with high incidence of associated anomalies and medical conditions. For this particular set of patients, percutaneous closure is a valid alternative. Asymptomatic or mildly symptomatic children should be treated at a later age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 29 publications
(36 reference statements)
5
33
0
Order By: Relevance
“…Though the Bergersen et al study does include a comprehensive listing of complications, it does not stratify patients and the complications according to patient size (7,17). In 1 study of 52 patients, the investigators reported no major complications, yet discussed 2 device embolizations that were classified as minor complications (6). Alone, these 2 would account for a nearly 4% major complication rate, which is more similar to our results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Though the Bergersen et al study does include a comprehensive listing of complications, it does not stratify patients and the complications according to patient size (7,17). In 1 study of 52 patients, the investigators reported no major complications, yet discussed 2 device embolizations that were classified as minor complications (6). Alone, these 2 would account for a nearly 4% major complication rate, which is more similar to our results.…”
Section: Discussionsupporting
confidence: 89%
“…These studies, however, were based on older and larger patients than are often referred today. There is very little published data on whether this complication rate holds true for the much younger and smaller patient; what is available is inconsistent in definition of major complications (5)(6)(7)(8). The most comprehensive data describing adverse event rates in congenital cardiac catheterization did not stratify results according to patient size (7).…”
mentioning
confidence: 94%
“…Present reports on transcatheter ASD closure in small children are scarce and only a few refer to the group with a body weight below 10 kg [6][7][8][9][10][11][12][13][14][15]. The population described in this study is one of the biggest groups treated by this method in the world.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Our patient faced a remarkable postinterventional clinical course. Postinterventional TEE demonstrated perfect device position after release, so we did not expect any clinical problems.…”
mentioning
confidence: 89%